2021
DOI: 10.9734/jpri/2021/v33i31b31708
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity Prevalence and Predictors in People Living in Karachi

Abstract: Objective: This study was aimed to establish the prevalence of overweight, obesity and related its factors among the citizens of Karachi. Methodology: From Jan 2018 to August 2018. This cross-sectional analysis was conducted to obtain information from 772 persons using a validated questionnaire and traditional height and weight evaluation methods have been used. Overweight and obesity were described by South Asian cut-off points as 23 ≥ BMI (Normal), 25.0 - 29.9 BMI (Overweight) and 30 ≤ BMI (Obese) resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Since 1980 global obesity has become triple in 2023. It is estimated that by 2030, globally 1 in 5 women and 1 in 7 men will have obesity (WHO, 2014;Ibrahim et al, 2021). More than 4.72 million people are dying each year due to obesity, which is about 8% of global deaths; the highest death is in Egypt, and the lowest death is in Japan (Yilmaz, 2017;WHO, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Since 1980 global obesity has become triple in 2023. It is estimated that by 2030, globally 1 in 5 women and 1 in 7 men will have obesity (WHO, 2014;Ibrahim et al, 2021). More than 4.72 million people are dying each year due to obesity, which is about 8% of global deaths; the highest death is in Egypt, and the lowest death is in Japan (Yilmaz, 2017;WHO, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal or excessive adipose tissue accumulation occurs when lipids accumulate in adipocytes due to an imbalance between intake and calorie expenditure, and these cause the risk of being overweight and obesity [ 1 ]. According to the World Health Organization in 2008, 1.4 billion adults were overweight, of which 500 million were obese [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both obesity and body stability offers the effort to bring the static and dynamic body close to equilibrium in vary conditions [12]. Several studies show that body mass index (BMI) has directly relationship with balance in static position as well as dynamic position but the category is not yet clear for physical activities and balance [13]. Physical activities (PA) at a higher level necessitate a higher degree of balance, hence physical activities and body mass index (BMI) have an impact on balance [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show that body mass index (BMI) has directly relationship with balance in static position as well as dynamic position but the category is not yet clear for physical activities and balance [13]. Physical activities (PA) at a higher level necessitate a higher degree of balance, hence physical activities and body mass index (BMI) have an impact on balance [12,13]. In a study which was conducted by Pollack and Chestin showed that obese people have higher risks of knee, hand, fingers, and wrist injuries when compared to healthy people [14].…”
Section: Introductionmentioning
confidence: 99%